The Relationship Between Depth of Vocabulary Knowledge and Chinese Non-English Majors’ L2 Lexical Inferencing Strategy Use and Success - Li, Junlong (CERJ, Faculty of Education, University of Cambridge, 2022)
The present study aims to explore the correlation between Chinese non-English majors’ depth of vocabulary knowledge (DVK) and their lexical inferencing strategy use and inferential success in English as a foreign language (EFL) reading comprehension. With Qian and Lin’s DVK framework (2020) and Nassaji’s classification of the lexical inferencing strategies (2003) as the theoretical foundation, this mixed methods study investigates 40 third-year non-English major participants, who are categorised into the low-intermediate DVK level (LIL) group and the high-intermediate DVK level (HIL) group. The major findings reveal that: (1) The HIL learners adopted more strategies of word associations, discourse knowledge, and world knowledge, while the LIL learners chose more strategies regarding homonymy, morphology, and sentence-level grammatical knowledge. (2) The HIL learners made more effective use of all types of strategies. However, when both groups utilised the strategies of word associations and sentence-level grammatical knowledge, the difference in their inferential success was not remarkable. (3) Participants’ different choices on strategy use were mainly caused by their understanding of vocabulary meanings and lexical collocations. The LIL learners tended to be attracted to the sound relationships, word forms, and sentence structures, whilst the HIL learners were adept at internalising mnemonic techniques, contextual clues, and their common sense, and thus they focused more on the relationship between unknown words and the whole text. (4) The HIL learners’ inferential success was attributed to both their richer accumulation of vocabulary meanings as well as collocations and their higher degree of risk taking in lexical inferencing. Findings of this study may help Chinese college English teachers effectively with the training of English vocabulary and reading by offering pedagogical implications for non-English majors’ DVK improvement and lexical inferencing strategy development.
Keywords: second language vocabulary learning; depth of vocabulary knowledge; lexical inferencing strategies; EFL reading comprehension; Chinese non-English major students